Modernization of Cominco's zinc plant and lead smelter at Trail, British Columbia (10278aa3-742e-4f4e-9e62-6cedf484fe18) - C. A. Sutherland (Canadian Institute of Mining, Metallurgy and Petroleum, 1988)
"Smelting of copper-gold ore from nearby Rossland mines started at Trail in the 1890s. As ore from the Rossland mines became exhausted, lead smelting of hand-sorted galena ore from other British Columbia mines was initiated. With the development of flotation technology for the separation of lead, zinc, and iron sulphides in the first two decades of this century, the large Sullivan orebody at Kimberley, British Columbia, became the f oundation for the growth of a major zinc and lead smelter at Trail. Lead smelting began in 1901, electrolytic zinc in 1916, and by 1984, the Trail metallurgical complex had produced 10 million tons of each metal. Its present capacity is 270000 tonnes per year of zinc and 110 000 tonnes/year of lead.This paper reviews the history of technological changes in the Trail production plants, emphasizing the zinc plant modernization program started in the 1970s, and also the planned introduction of the QSL oxygen lead smelting process in the late 1980s. Lead modernization will increase production capacity to a maximum of 160000 tonnes per year.IntroductionCopper-gold ore was discovered at Rossland, British Columbia, in the year 1890, starting a mining industry that was to last over three decade s. Selected ore was at first transported at high cost to distant U.S. smelters, so there naturally followed a decision to construct a small copper smelter to process the local ore to matte. It was built in 1896 at the mouth of Trail Creek on the Columbia River, about 10 km from Rossland. This little smelter was to develop and diversify in the next 90 years into the world 's largest lead-zinc producer).The mining boom that occurred in the northwestern United States and southeastern British Columbia in the period of 1890 to 1910 saw the brief operation of many small local smelters. The only one to survive was the smelter at Trail. The circumstances that permitted its continued life and subsequent growth, form a fascinating history of business deals, litigation, andsteady technical progress.Early investment in local railway transportation and options by F.A. Heinze, the smelter' s founder, attracted the attention of the Canadian Pacific Railway Company, which purchased Heinze' s assets in 1898. This provided the capital base for survival and growth of the smelter, which remained and prospered under the Canadian Pacific umbrella for almost ninety years. It was registered as the Consolidated Mining and Smelting Company of Canada Limited in 1906; in 1966, this name wasshortened to Cominco Ltd.The Rossland mines continued to supply copper ore for the smelter until the late 1920s, but lead-silver ore also became available from the contemporary mining boom in the Slocan area, about 80 km away. In 1901, the Trail smelter diversified into lead; and when the CM&S Co. acquired the St. Eugene Mine at Moyie and the Sullivan Mine at Kimberley, the smelter was guaranteed a firm supply of lead ore. The company also purchased the West Kootenay Power and Light Company, which even before the turn of the century had constructed the first of four hydroelectric generating plants on the Kootenay River near Trail. This acquisition assured the CM&S smelter and its local mines of a stable power supply and the opportunity to diversify into power intensive technology."